indiana illustrated classics: the invisible man - Wells , H.G; H.G Wells (India Indiana publishing house, 2008)
The Invisible Man by H.G. Wells, often featured in illustrated classics collections, is a science fiction story about a scientist named Griffin who discovers the secret of invisibility but descends into madness and crime.
English